Broken Music : Artists' Recordworks. - Adorno, Theodor W.; Block, René; Block, Ursula; Dubuffet, Jean; Glasmeier, Michael; Knizak, Milan; Moholy-Nagy, Laszlo; Zeller, Hans Rudolf (Berlin : Daadgalerie Berlin, 1989)
Abramovic, Marina & Ulay ; Acconci, Vito ; Adams, Lewis Mac ; Adams, Yura ; Adler, Jeremy ; Agam, Yaacov ; Agnetti, Vincenzo ; Albert-Birot, Pierre ; Alberto Savinio & George Antheil ; Allen, Jo Harvey ; Altagor ; Altman, Patrick ; Amirkhanian, Charles ; Anderson, Beth ; Anderson, Laurie ; Anonymus ; Antheil, George ; Antin, Eleanor ; Apollinaire, Guillaume ; Appel, Karel ; Apple, Jacki ; Applebroog, Ida ; Arcand, Pierre-André ; Arias-Misson, Alain ; Armajani, Siah ; Arman ; Arp, Hans (Jean) ; Art & Language ; Art by Telephone ; Art, Alma ; Artaud, Antonin ; Artists' Jazz Band ; Artschwager, Richard ; Ashley, Robert ; Aslins, Elena ; Atkinson, Conrad ; Attersee, Christian Ludwig ; Azeredo, Ronaldo ; Baacke, Rolf-Peter ; Babel, Tara ; Bakhchanyan, Vagrich ; Baldessari, John ; Balestrini, Nanni ; Ball, Hugo ; Balla, Giacomo ; Ballabeni, Franco ; Balthaus, Fritz ; Barbara, Joan La ; Baren, Peter ; Barg, Barbara ; Baroni, Vittore ; Barry, Robert ; Bartlett, Jennifer ; Bärtschi, Werner ; Baschet, Bernard & François ; Bates, Bob ; Baumann, Katharina ; Baxter, Iain ; Bean, Anne ; van Bebber, Claus ; Becker, Konrad ; Beckley, Connie ; Bedaux, Jacoba ; Bekaert, Jacques ; Bell, Grace ; van Bemmel, Marcelle ; Ben ; Bender, John ; Bense, Max ; Berberian, Cathy ; Bergamini, Giacomo ; Bernstein, Alex ; Bertini, Giani ; Bertoia, Harry ; Bertrand, Jean-Pierre ; Beuys, Joseph ; Bianchi, Maurizio ; Bielz, Gudrun ; Bijl, Guillaume ; Bisset, Bill ; Björn, Roth ; Blaine, Julien ; Blake, Peter ; Bleus, Guy ; Blum, Eberhard ; Blumenschein, Tabea ; Bob & Bob ; Bochner, Mel ; Bodde, Jan ; Bodde, Sievert ; Bodin, Lars-Gunnar ; Bodin, Svante ; Boegel & Holtappels ; Bogosian, Eric ; Böhmler, Claus ; Boltanski, Christian ; Bonis, John ; Bonk, Ecke ; Borillo, Mario ; Borofsky, Jonathan ; etc.
Broken Music : Artists' Recordworks, daadgalerie Berlin / Gemeentemuseum Den Haag / Magasin Grenoble, 1989
Duits
Duits & Engels & Frans
Engels
Frans
boek